Efektivitas Promosi Produk Bakmi GM Melalui Media Sosial Instagram @Bakmigmania Menggunakan Pendekatan AIDA - Widya Safeeya Ningrum; Agung Kresnamurti Rivai P; Meta Bara Berutu (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the effectiveness of Bakmi GM promotion if evaluated using the AIDA model. The method used in this study is qualitative research with a descriptive method, where data is collected through interviews, documentation, and observation. The sources in this study consisted of 13 key informants who were consumers of Bakmi GM and employees of Bakmi GM. The data analysis technique used in this study was interactive data analysis, namely data collection, data reduction, data presentation, and conclusions or verification. The results of the study found that Bakmi GM's promotional strategy on Instagram has been effective in implementing the AIDA model, although the frequent upload frequency and the lack of completeness of the description in the product discount uploads were complaints for informants.